Język Włatców móch i jego wpływ na błędy językowe młodzieży szkolnej (Conversatoria Linguistica, 2019)
The main aim of the article is to show the influence of language mistakes within the written language of Włatców móch on language culture and linguistic mistakes of school youth. Nowadays, young people are particularly exposed to mass culture, which is characterized by the desire to reduce the standard language norm to a usable standard. Fashion breaking standards have a major impact on the language behavior of young people. In addition, the dynamic economic and cultural transformations present today’s society in new situations in which everyone must find themselves.As I have shown, functional illiteracy is perceived as a big problem in the developed countries of North America and Europe. Poland is located at one of the lower levels of literacy. Only 3%–7% of adult Polish have a high level of literacy. On the other hand, 15-year studies have shown that every tenth person is with functional illiteracy, and only 6% haven’t problems with receiving and processing information.